The gift of fear : survival signals that protect us from violence - De Becker, Gavin (New York : Delta, 1999)
From the Publisher: True fear is a gift. Unwarranted fear is a curse. Learn how to tell the difference. A date won't take "no" for an answer. The new nanny gives a mother an uneasy feeling. A stranger in a deserted parking lot offers unsolicited help. The threat of violence surrounds us every day. But we can protect ourselves, by learning to trust-and act on-our gut instincts. In this empowering book, Gavin de Becker, the man Oprah Winfrey calls the nation's leading expert on violent behavior, shows you how to spot even subtle signs of danger-before it's too late. Shattering the myth that most violent acts are unpredictable, de Becker, whose clients include top Hollywood stars and government agencies, offers specific ways to protect yourself and those you love, including-how to act when approached by a stranger-when you should fear someone close to you-what to do if you are being stalked-how to uncover the source of anonymous threats or phone calls-the biggest mistake you can make with a threatening person and more. Learn to spot the danger signals others miss. It might just save your life.
In the presence of danger -- Technology of intuition -- Academy of prediction -- Survival signals -- Imperfect strangers -- High-stakes predictions -- Promises to kill (understanding threats) -- Persistence, persistence (dealing with people who refuse to let go) -- Occupational hazards (violence in the workplace) -- Intimate enemies (domestic violence) -- I was trying to let him down easy (date stalking) -- Fear of children (violent children) -- Better to be wanted by the police than not to be wanted at all (attacks against public figures) -- Extreme hazards -- Gift of fear -- Epilogue -- Acknowledgments -- Appendixes -- Recommended reading -- Index.
Includes index.
"A Dell trade paperback."
Keywords: Violence -- Psychological aspects; Victims of crimes -- Psychology; Women -- Crimes against; Violent crimes -- Psychological aspects; Fear; Intuition; Crime Victims -- psychology; Fear; Intuition; Psychology, Social; Violence